Red Cell Distribution Width Identifies Cerebral Venous Sinus Thrombosis in Patients With Headache. (May 2015) - Demir, Recep; Saritemur, Murat; Ozel, Lutfi; Ozdemir, Gokhan; Emet, Mucahit; Ulvi, Hızır
Background: Diagnosing cerebral venous sinus thrombosis (CVST) in patients referring to emergency service or neurology outpatient unit with complaints of headache is a challenging task. Magnetic resonance (MR) venography is the gold standard, but there are limitations regarding its use. Aim: To evaluate the validity of red cell distribution width (RDW) in CVST diagnosis in patients presenting with headache. Methods: A total of 138 patients comprising 37 patients with CVST and 101 control primer headache cases were included in this retrospective cross-sectional study. Control group consists of hospitalized patients with primary headache. Venous blood hemoglobin (Hb), platelet, mean corpuscular volume (MCV), RDW, fibrinogen, and vitamin B12 levels of the patients were recorded at the first referral. Diagnosis of CVST was established by MR venography. Results: The RDW ratio of patients with a diagnosis of CVST was significantly higher than that in patients with primary headache (15.3 ± 1.4 vs 13.3 ± 0.5; P <.0001). Fibrinogen and vitamin B12 levels were not significantly different between the 2 groups. In a total of 11 patients, there was more than 1 thrombosis. In 21 of the patients with CVST, gene mutation was detected. There was no significant difference between the patients with and without mutations regarding RDW values. Diagnostic validity of RDW was found to be excellent in differentiating patients with CVST and primary headache (area under the curve = 0.996; 95% CI: 0.990-1.000). Optimum RDW cutoff value was determined as 14.1% (sensitivity: 91.9%, specificity: 99%, positive predictive value: 92.8, negative predictive value: 0.082). Conclusion: We suppose that among patients presenting with the complaint of headache, RDW value may lead to diagnose CVST.